2018
DOI: 10.18332/tid/84122
|View full text |Cite
|
Sign up to set email alerts
|

Building on the success of ten years of comprehensive smokefree legislation in England

Abstract: Innovations in media educational campaigns and health warning labels on cigarettes and other tobacco productsFO-329-3 Over-time changes in reactions to pictorial health warning labels and association with quitting behavior among adult smokers in Thailand: findings from ITC Thailand survey (2005 -2012

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The 14 included papers, [23][24][25][26][27][28][29][30][31][32][33][34][35][36] reported 13 mass-media campaigns implemented between 2002 and 2019 in eight countries (Vietnam, China, U.S., England, Scotland, Indonesia, Bosnia and Herzegovina, and Ukraine). These studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36] evaluated mass media campaigns using pre-and post-campaign surveys or semi-structured interviews, [23][24][25][26][27][28][29]34] ecological studies (e.g., hospital admissions, Quitline call volume data), [33,35] not clearly described, [30,31] or social media metrics data [32,36]. The grey literature search located 61 mass media campaigns [12,17, from 44 countries implemented between 2016 and 2022.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 14 included papers, [23][24][25][26][27][28][29][30][31][32][33][34][35][36] reported 13 mass-media campaigns implemented between 2002 and 2019 in eight countries (Vietnam, China, U.S., England, Scotland, Indonesia, Bosnia and Herzegovina, and Ukraine). These studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36] evaluated mass media campaigns using pre-and post-campaign surveys or semi-structured interviews, [23][24][25][26][27][28][29]34] ecological studies (e.g., hospital admissions, Quitline call volume data), [33,35] not clearly described, [30,31] or social media metrics data [32,36]. The grey literature search located 61 mass media campaigns [12,17, from 44 countries implemented between 2016 and 2022.…”
Section: Study Selectionmentioning
confidence: 99%
“…Of these campaigns, two campaigns [26,36] assessed viewer perceptions of smoke-free campaign messagingloss-framed (i.e., demonstrating the risks of SHS) versus gain-framed (i.e., demonstrating the benefits of smokefree environments) advertisements. A 2010 U.S. based campaign found that loss-framed advertisements had higher emotional impact than gained framed advertisements (68% vs. 58%, p < 0.001) but gain-framed advertisements were more likely to be recalled than loss-framed C, A, S Vietnam [28,40,55,82], China [29,56,94], UK [24,25,27,31,43,72,80], US [23,26,33,38,48], Indonesia [30,36], Bosnia and Herzegovina [32], Ukraine [34,59], United Arab Emirates [86], Cuba [90], Jordan [89], India [50,92], Japan [69,87], Qatar [91], Luxembourg [88], Nepal [93], New Zealand [51,62], Belarus [74], Hong Kong [77],…”
Section: Awareness Of Campaignmentioning
confidence: 99%